Independent attacks in imperfect settings: a case for two-way quantum key distribution scheme - Shamsul Shaari, Jesni; Bahari, Iskandar (Elsevier, 2010)
We review the study on a two-way quantum key distribution protocol given imperfect settings through a simple analysis of a toy model and show that it can outperform a BB84 setup. We provide the sufficient condition for this as a ratio of optimal intensities for the protocols.